KOMPETENSI DAN KINERJA GURU SEKOLAH DASAR NEGERI DI GUGUS 5 LULUT KLAPANUNGGAL-BOGOR - Horiz, Abdul Wahid; Kamil, Mustafa; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to determine the effect of the use of the Merdeka Mengajar (PMM) Platform on the performance of public elementary school teachers in Cluster 5 Lulut, Klapanunggal District, Bogor Regency. The background of this research is based on the importance of improving teacher quality and professionalism in facing the changing paradigm of national education, particularly in the implementation of the Merdeka Curriculum, which demands teachers to be more adaptive, reflective, and innovative. PMM is a digital platform designed to support the independent and sustainable development of teacher competencies. This study used a qualitative descriptive approach with a case study method. Data collection techniques were carried out through observation, in-depth interviews with teachers, principals, and supervisors, and documentation of teacher activities in using PMM. The data obtained were analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the use of PMM contributes significantly to improving teachers' pedagogical, professional, social, and personal competencies. PMM helps teachers design more contextualized learning, implement differentiated learning, engage in self-reflection, and build professional collaboration. Furthermore, the PMM also plays a role in integrating teacher performance data through activity documentation features, automated reporting, and connectivity with the SIASN system, which supports objective and structured teacher performance assessments. The conclusion of this study is that the PMM has a positive impact on improving overall teacher performance. Therefore, strengthening institutional support and technical training is needed to optimize and equitably utilize the PMM across all educational units. Keywords: Merdeka Mengajar Platform, Metacognitive Awareness, Teacher Competence, Teacher Performance, Merdeka Curriculum.